Personality and democratic politics (Berkeley University of California Press, 1975)
Draws on research in social psychology, political science and other disciplines to explore connections between personality, political beliefs, and political leadership.
Meaning and measurement of self-esteem -- Syndrome of self-esteem -- Acquisiton of political knowledge -- Democratic commitment and the democratic personality -- Idea of compensation -- Participation and political leadership.
Includes index.
Bibliography: p. [337]-358.
Keywords: Personality and politics; Personnalitâe et politique; Politische Beteiligung; Politische Psychologie; Personality and politics